Implementasi Metode K-Means untuk Pembuatan Aplikasi Monitoring Kedisiplinan Karyawan pada PT. Sekurindo Duta Utama Perkasa - Ali Azun Manalu; Rahmawati (CV. Multi Kreasi Media, 2026)
PT. Sekurindo Duta Utama Perkasa is a security services company committed to providing the best security services for various sectors, including offices, industry, banking, shopping centers, and residential areas. However, PT. Sekurindo Duta Utama Perkasa faces challenges in efficiently monitoring and evaluating employee discipline levels. The manual monitoring process makes it difficult for management to identify employees who demonstrate good performance and those who frequently violate regulations. Along with technological developments, the use of data mining methods such as K-Means Clustering can be an effective solution in grouping employees based on their discipline levels. By implementing this method in a monitoring application, companies can easily identify employee behavior patterns, increase evaluation transparency, and provide appropriate actions for employees who need further coaching. The application of the K-Means method has proven effective in supporting more targeted analysis and increasing operational efficiency and strengthening the basis for management decision-making regarding rewards and punishments, training, or other HR strategies.